AMTS: NCAR/NSF C-130 Low Rate (1 sps) Navigation, State Parameter, and Microphysics Flight-Level Data [NCAR/EOL] - UCAR/NCAR - Earth Observing Laboratory (Arctic Data Center)
This dataset contains NetCDF data obtained aboard the NSF/NCAR C-130 aircraft during the Arctic Mesopause Temperature Study (AMTS) project. This dataset contains the Low Rate (LRT, 1sps) Flight Level production data.